Prenatal exposure to Plasmodium falciparum increases frequency and shortens time from birth to first clinical malaria episodes during the first two years of life: prospective birth cohort study. (December 2016) - Sylvester, Boniphace; Gasarasi, Dinah; Aboud, Said; Tarimo, Donath; Massawe, Siriel; Mpembeni, Rose; Swedberg, Gote
Abstract Background Prenatal exposure toPlasmodium falciparum affects development of protective immunity and susceptibility to subsequent natural challenges with similar parasite antigens. However, the nature of these effects has not been fully elucidated. The aim of this study was to determine the effect of prenatal exposure toP. falciparum on susceptibility to natural malaria infection, with a focus on median time from birth to first clinical malaria episode and frequency of clinical malaria episodes in the first 2 years of life. Methods A prospective birth cohort study was conducted in Rufiji district in Tanzania, between January 2013 and December 2015. Infants born to mothers withP. falciparum in the placenta at time of delivery were defined as exposed, and infants born to mothers withoutP. falciparum parasites in placenta were defined as unexposed. Placental infection was established by histological techniques. Out of 206 infants recruited, 41 were in utero exposed toP. falciparum and 165 infants were unexposed. All infants were monitored for onset of clinical malaria episodes in the first 2 years of life. The outcome measure was time from birth to first clinical malaria episode, defined by fever (≥37 °C) and microscopically determined parasitaemia. Median time to first clinical malaria episode between exposed and unexposed infants was assessed using Kaplan–Meier survival analysis and comparison was done by log rank. Association of clinical malaria episodes with prenatal exposure toP. falciparum was assessed by multivariate binary logistic regression. Comparative analysis of mean number of clinical malaria episodes between exposed and unexposed infants was done using independent samplet test. Results The effect of prenatal exposure toP. falciparum infection on clinical malaria episodes was statistically significant (Odds Ratio of 4.79, 95 % CI 2.21–10.38, p < 0.01) when compared to other confounding factors. Median time from birth to first clinical malaria episode for exposed and unexposed infants was 32 weeks (95 % CI 30.88–33.12) and 37 weeks (95 % CI 35.25–38.75), respectively, and the difference was statistically significant (p = 0.003). The mean number of clinical malaria episodes in exposed and unexposed infants was 0.51 and 0.30 episodes/infant, respectively, and the difference was statistically significant (p = 0.038). Conclusions Prenatal exposure toP. falciparum shortens time from birth to first clinical malaria episode and increases frequency of clinical malaria episodes in the first 2 years of life.